(untitled) (American Journal of Islam and Society, 1989)
Stephen Humphreys’ Islamic History: a Framework for Inquiry represents a new approach to the old problem of the historian and his sources. Following the current trend among Western scholars ofislam and of history in general, Humphreys ’lays much more emphasis on the methodology of dealing with pre-modern historical sources than on establishing the "facts" to get at the "truth." This is because of Humphreys’ belief, widely shared by historians today, that before we can learn any facts, we must understand our sources, their uses and their inadequacies, and that before we can understand the sources, we must arrive at a methodology that is universally acceptable, at least in its broad outJine. With reference to mecljeval Islamic history, these needs are all the more acute, because there has been little systematic thought given to methodology, except in a few introductory pages in the work of certain scholars, and because the sources themselves present so many problems. Owing to these considerations, Humphreys’ book focuses on methodology, contains no narrative history and is intended for the student of history or one of its allied fields rather than the layman. The book covers the period of medieval Islamic history, which is defined as 600-1600 CE. The reason for continuing to use this conventional and widely-accepted division is that the source material fundamentally changes in quality for the period after 1500 because of the survival of Ottoman archival material subsequent to that date (p. 9). This seems reasonable, for the lack of contemporary documents for the medieval Islamic period imposes a greater reliance on non-literary epigraphic and archaeological evidence, as well as traditional literary sources which are usually not contemporary with the events described, leading in tum to a different methodology than that of modem social science. On the other hand, one must remember that the study of history should not mold itself simply according to the dictates of what is and is not available in the sources, for that could exaggerate the distortions to which our information is already subject. AJso, we should not forget that artificial periodizations may obscure the real continuity of the flow of history and impair our ability to see its unifying features. Nevertheless, the atomization of history did not begin with Humphreys, whose methodology rather tends to unify Islamic history by seeing similar patterns in and drawing comparisons between widely divergent times and places. To demonstrate his methodology, Humphreys divides his work into two parts. The first part consists of two chapters covering modem reference works and the medieval sources of evidence generally, while the second part contains ten chapters. each dealing with a broad problem of Islamic history and detailing the sources relevant to that problem. Humphreys’ strong bibliographical emphasis makes his work most closely resemble Jean Sauvaget’s Introduction to the History of the Muslim East (Berkeley and Los Angeles: University of California Press, 1965), as revised by Claude Cahen, a work which Humphreys himself refers to as "the best overview we have of Islamic historical studies" (p. 20) . Sauvaget, however, was selective, whereas Humphreys aims to be comprehensive, and to a large extent succeeds. Because it is both broader and more recent, Humphreys’ work supersedes the earlier book. As a general annotated bibliography, Humphreys’ work is certainly a useful resource for students of Islamic history ...